Applying program comprehension techniques to karel robot programs - Oliveira, Nuno (2009)
In the context of program understanding, a challenge research topic 1 is to learn how techniques and tools for the comprehension of General-Purpose Languages (GPLs) can be used or adjusted to the understanding of Domain-Specific Languages (DSLs). Being DSLs tailored for the description of problems within a specific domain, it becomes easier to improve these tools with specific visualizations (at a higher abstraction level, closer to the problem level) in order to understand the DSLs programs. In this paper, comprehension techniques will be applied to Karel language. This will allow us to explore the creation of problem domain visualizations for this language and to combine both problem and program domains in order to reach a full understanding of Karel programs.